FREE CASH FLOW DAN ASIMETRI INFORMASI TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERTAMBANGAN YANG TELAH TERDAFTAR DI BEI PERIODE 2015-2020 - Aisyah Prastiani Sofyana Hamzah; Siti Saadah; Jaya Mustika (Jurnal Akuntansi, Auditing dan Keuangan Syariah, 2022)
Earnings management is an effort made by management to manipulate accounting numbers reported to external parties with the aim of benefiting themselves by changing or ignoring established accounting standards, thus presenting untrue information. The variables of Free Cash Flow and Information Asymmetry are estimated to have an influence on Earnings Management. This study aims to determine the effect of Free Cash Flow and Information Asymmetry on Earnings Management. The dependent variable in this study is Earnings Management which is measured using the Modified Jones Model, while the independent variables in this study are Free Cash Flow and Information Asymmetry. This study also uses the control variables Firm Size and Firm Age as a controller so that the relationship between the independent variable (independent variable) and the dependent (dependent variable) is not influenced by external factors that are not examined. This study uses secondary data in annual reports published by companies on the Indonesia Stock Exchange. The population in this study are mining companies listed on the Indonesia Stock Exchange for the 2015-2020 period, which are 47 companies. The sampling technique used in this study is purposive sampling so that the number of samples obtained is 9 companies. The results of this study indicate that Free Cash Flow has an effect on earnings management and information asymmetry has no effect on earnings management.